A benchmark for evaluation of algorithms for identification of cellular correlates of clinical outcomes. (8th October 2015) - Aghaeepour, Nima; Chattopadhyay, Pratip; Chikina, Maria; Dhaene, Tom; Van Gassen, Sofie; Kursa, Miron; Lambrecht, Bart N.; Malek, Mehrnoush; McLachlan, G. J.; Qian, Yu; Qiu, Peng; Saeys, Yvan; et al.
Abstract: The Flow Cytometry: Critical Assessment of Population Identification Methods (FlowCAP) challenges were established to compare the performance of computational methods for identifying cell populations in multidimensional flow cytometry data. Here we report the results of FlowCAP‐IV where algorithms from seven different research groups predicted the time to progression to AIDS among a cohort of 384 HIV+ subjects, using antigen‐stimulated peripheral blood mononuclear cell (PBMC) samples analyzed with a 14‐color staining panel. Two approaches (FlowReMi.1 and flowDensity‐flowType‐RchyOptimyx) provided statistically significant predictive value in the blinded test set. Manual validation of submitted results indicated that unbiased analysis of single cell phenotypes could reveal unexpected cell types that correlated with outcomes of interest in high dimensional flow cytometry datasets. © 2015 International Society for Advancement of Cytometry